IS THERE A PLACE FOR CENTRAL-EASTERN EUROPE IN POSTCOLONIAL SPACE? POSSIBILITIES OF JOURNEY TRAJECTORIES - Kołodziejczyk, Dorota (Porównania, 2013)
I ask in my article a question about the usability of some postcolonial developments in theorizing/conceptualizing Central and Eastern European cultures, nations and postcommunist transitions. I am less interested in evaluating the adequacy of such developments, and more in examining what trajectories can be forged by such redirection of postcolonial vectors. We are used to discussing the sense and productivity of given postcolonial paradigms into the Central and Eastern European contexts, however, the concomitant issue of how such inflections of postcolonialism encourage further theorization of the region in broader global context remains largely untouched. While applying postcolonial paradigms to the problems of dependence, European/Russian/Soviet imperialism, anti-communist resistance and postcommunist transformations has proved productive and truly justified, even necessary in many cases, it’s difficult not to have an impression that a crucial, larger framework is missing in such developments. For example, what challenges are posed to postcolonial studies in such uses? What particular contribution can be made in these developments to the discussions of modernity and its peripheral or alternative realizations outside the West? What possible new transnational solidarities and ecumenes does such postcolonial reconfiguration of thinking about Central and Eastern Europe promise? What forms of remembrance does it necessitate in memory cultures of late modernity? How can it challenge the Eurocentric or West-centric traits in contemporary academic and political discourses, their strategies of containment, omissions and repressions? How can a dialogue ensue from the above rather than a monologism of victimhood? These and other related questions ultimately concern the problem of locating the region in critical globalization discourses